BATTERED, BUT UNBROKEN: EPISTEMOLOGICAL AND THEORETICAL CHALLENGES TO WESTERN IR THEORY (REALISM AND WORLD SYSTEMS THEORY) - Terry McDonald (European Scientific Journal, ESJ, 2014)
Recent developments in the field of International Relations have called into question the nature of the dominant theories used therein. IR has been painted as suffering from an inherent Western bias. This paper does not dispute this fact, but argues that IR scholars must now move forward by acknowledging this bias. Western IR theories can maintain utility, but it must be in a context of knowing the limits associated with their origins.